Nanocomposite in Paediatric Dentistry – A Systematic Review - S, Rasveya; Kumar, Dinesh (Journal of Neonatal Surgery, 2024)
Background:Nanotechnology has revolutionized modern dentistry by introducing nanocomposite materials with enhanced physicochemical and biological properties. In pediatric dentistry, where durability, biocompatibility, and patient compliance are critical, nanocomposites offer promising advantages over conventional restorative materials. Aim: This systematic review aims to evaluate the clinical performance, applications, and effectiveness of nanocomposites in pediatric dentistry. Materials and Methods: A comprehensive literature search was conducted using electronic databases including PubMed, Google Scholar, PsycINFO, and the Cochrane Library. Relevant studies were identified using keywords such as “nanocomposite,” “pediatric dentistry,” and “dental restoration.” Studies were screened based on predefined inclusion and exclusion criteria. A total of 11 clinical studies were included after quality assessment using the Cochrane Risk of Bias tool and Newcastle Ottawa Scale. Results: The included studies demonstrated that nanocomposites exhibit superior mechanical strength, improved wear resistance, and enhanced aesthetic properties. They also showed antibacterial effects, reduced biofilm formation, and decreased incidence of secondary caries. Clinical outcomes such as retention, marginal integrity, and postoperative sensitivity were either improved or comparable to conventional restorative materials. However, some studies reported no statistically significant differences in long-term performance. Conclusion: Nanocomposites represent a significant advancement in pediatric restorative dentistry, offering improved clinical performance and patient outcomes. Despite their promising potential, further long-term, large-scale clinical trials are necessary to establish their safety, cost-effectiveness, and superiority over traditional materials